Simple algorithms for selecting an energy-efficient server in a cluster of servers. (2018) - Duolikun, Dilawaer; Kataoka, Hiroki; Enokido, Tomoya; Takizawa, Makoto
Electric energy consumed by computers, especially servers in scalable clusters has to be reduced to realise eco society. In this paper, we first propose a multi-level power consumption (MLPCM) model which gives how much electric power a server consumes to perform application processes. We also propose an multi-level computation (MLCM) model which shows the expected execution time of an application process performed on a server. By using the MLPCM and MLCM models, we propose a pair of simple locally energy-aware (SLEA) and simple globally energy-aware (SGEA) algorithms to select a host server to perform an application process issued by a client. In the SLEA algorithm, a host server is selected, which is expected to consume the minimum electric energy to perform the process. In the SGEA algorithm, a host server is selected, where the total expected electric energy consumption of not only the host server but also the other servers is minimum. In the evaluation, we show the total electric energy consumption and active time of servers and the average execution time of processes can be reduced in the SGEA algorithm compared with other algorithms.